Assessing the implementation of wildfire mitigation initiatives for the protection of villages in Portugal - Ana Gonçalves; Sandra Oliveira; José Luís Zêzere (Trees, Forests and People, 2025)
Since 2017, several initiatives have been created in Portugal to enhance wildfire resilience by protecting people and assets, promoting fuel management, and reducing vegetation density and continuity near built-up areas. This study analyzed how the “Safe Villages” and ''Safe People'' programs, launched in Portugal in 2018, have been implemented in relation to the territorial and demographic characteristics of the villages. For that, eight municipalities were chosen as study area, spanning three Portuguese regions prone to wildfires (Caramulo Mountain, Pinhal Interior Norte Sub-Region, and Algarve). Four biophysical parameters were analyzed (the percentage of critical hazardous area, forest and shrubland cover, slopes over 20°, and the number of times burned – proxy to burn recurrence) within the Village Protection Zone (100m-buffer surrounding built-up areas), together with population density. To assess the similarity of the analyzed characteristics between villages with and without implemented SV programs, The Mann-Whitney test was employed. A total of 166 SV were analyzed, with Alcoutim being the municipality with the highest number of SV implemented (84). The Mann-Whitney test results reveal no significant differences (p > 0.05) in population density and forest/shrubland percentages between SV and non-SV. However, statistically significant differences (p < 0.05), were found in the percentage of critical area with SV villages showing lower hazard levels (mean < 15 %), and in burn recurrence, with SV villages presenting a higher number of past fires (mean > 0.8 times burned).This suggests that other factors not included in the analysis (historic events and local resources), have contributed to the decision-making process for SV placement. Therefore, a primary objective should be to improve collaboration between entities and local communities to enhance the implementation and operation of such programs.